2011
DOI: 10.1093/infdis/jir193
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 28B Gene Variation at rs12979860 Determines Early Viral Kinetics During Treatment in Patients Carrying Genotypes 2 or 3 of Hepatitis C Virus

Abstract: Single-nucleotide polymorphisms upstream of the interleukin 28B (interferon λ3) gene (IL28B) strongly influence treatment efficacy in patients carrying hepatitis C virus (HCV) of genotype 1. In patients receiving 12 or 24 weeks of interferon-ribavirin therapy for infection with genotype 2 or 3 (n = 341), we found that rs12979860 strikingly determined the first phase of viral elimination (P < .001). In patients treated for 24 weeks, rs12979860 also predicted the rate of sustained virologic response (P = .02), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 13 publications
2
46
0
Order By: Relevance
“…Subsequent studies have successfully validated these findings in both genotype 1 19 and genotype2 and 3 infected patients from different ethnic groups. [20][21][22] There are differences in the strength of the association as well as predicted relationship to SVR depending on the viral genotype. Association studies on genotypes 2 and 3 have shown inconsistent results so far.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have successfully validated these findings in both genotype 1 19 and genotype2 and 3 infected patients from different ethnic groups. [20][21][22] There are differences in the strength of the association as well as predicted relationship to SVR depending on the viral genotype. Association studies on genotypes 2 and 3 have shown inconsistent results so far.…”
Section: Introductionmentioning
confidence: 99%
“…The decision tree in Figure 1 models the health state pathways (and the corresponding costs and transition probabilities) for the SOC therapy regimens implemented in the studies by Sarrazin (2011) [7] and Lindh (2011) [14]. For modeling the Sarrazin study, the treatment arms were stratified by HCV genotype, while the treatment arms modeling the study by Lindh were stratified by the duration of therapy, which was either 12 or 24 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Pretreatment variables that predict SVR in HCV-G3 patients are fibrosis stage (≤ F2), age less than 40 years, white ethnicity, female sex, basal viral load below 400,000 IU/mL, weight less than 85 kg, coffee consumption, and absence of steatosis. As in G2, the IFNL3 polymorphism seems to only predict RVS in patients who do not achieve RVR 52,54…”
Section: Treatment Of Hcvmentioning
confidence: 98%